Pijuayo (Bactris gasipaes) Pulp and Peel Flours as Partial Substitutes for Animal Fat in Burgers: Physicochemical Properties - Arteaga Miñano, Hubert Luzdemio (2024)
This study aimed to evaluate the incorporation of peach palm (PP) pulp and peel flours as substitutes for animal fat (25 and 50% substitution) in beef-based burgers. Incorporation of PP flours reduced hardness, springiness, cohesiveness, chewiness, fat, cooking losses, and diameter reduction. Burgers made with PP peel flour stood out for having low values of lipid oxidation in the two levels of fat substitution (0.14–0.23 malondialdehyde/kg) (p < 0.05). PP fruit has the potential to be utilized as a new ingredient in burgers, but future studies are needed regarding detailed sensory trials and consumer acceptance.